Status of postgraduate training in the livestock sector in South Asia and priorities for ILRI’s support - Ibrahim, M. (International Livestock Research Institute, 2010)
In order to establish the priorities for collaborative capacity strengthening activities of the learning institutes in the areas of animal production and veterinary services, ILRI commissioned five studies covering the following subregions: Eastern and Central Africa (ASARECA region); Southern Africa (SADC region), West Africa (CORAF region); South Asia; and Southeast Asia. This report summarizes the findings of the gap analysis study for the South Asia region. ILRI will make every effort to share and validate these findings and use this information in designing and implementing capacity strengthening activities in this region.